2020
DOI: 10.1016/j.ijppaw.2020.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Sarcocystis infection in red deer (Cervus elaphus) with eosinophilic myositis/fasciitis in Switzerland and involvement of red foxes (Vulpes vulpes) and hunting dogs in the transmission

Abstract: Red deer ( Cervus elaphus ) carcasses showing grey-greenish discolouration have been increasingly observed in the canton of Grisons, Switzerland. We investigated whether Sarcocystis infections were associated with this pathology, and whether wild and domestic canids were involved in their transmission. Meat from affected red deer ( n = 26), faeces and intestines from red foxes ( Vulpes vulpes ) ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 47 publications
(162 reference statements)
1
17
0
Order By: Relevance
“…Usually, molecular analysis is performed when oocysts/sporocysts of Sarcocystis spp. are microscopically detected in intestine mucosal or faecal samples [ 2 , 29 , 30 , 31 ]. However, the results of the present study reveal that molecular methods should be applied in testing all examined samples rather than only microscopically positive ones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, molecular analysis is performed when oocysts/sporocysts of Sarcocystis spp. are microscopically detected in intestine mucosal or faecal samples [ 2 , 29 , 30 , 31 ]. However, the results of the present study reveal that molecular methods should be applied in testing all examined samples rather than only microscopically positive ones.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, molecular methods have been applied for the identification of Sarcocystis spp. from fecal or mucosal scraping samples of various wild predators or scavengers infected under natural conditions [ 2 , 29 , 30 , 31 ]. The present work is the first study of the molecular identification of Sarcocystis spp.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it has long been postulated that red foxes and hunting dogs may play the final host role in the life cycle of Sarcocystis species affecting cervids, but for several species the exact final hosts are still unknown or are only suspected (Basso et al, 2020). In this context, based on molecular results and less consistent (98.8-99.1%) sequence identities, it was suggested that domestic dogs may be the final hosts of Sarcocystis linearis and/or Sarcocystis taeniata (Basso et al, 2020).…”
mentioning
confidence: 99%
“…In particular, it has long been postulated that red foxes and hunting dogs may play the final host role in the life cycle of Sarcocystis species affecting cervids, but for several species the exact final hosts are still unknown or are only suspected (Basso et al, 2020). In this context, based on molecular results and less consistent (98.8-99.1%) sequence identities, it was suggested that domestic dogs may be the final hosts of Sarcocystis linearis and/or Sarcocystis taeniata (Basso et al, 2020). Similarly, while tissue cysts of a Sarcocystis species with band-like protrusions were reported to be infective for the dog during experimental feeding (Poli et al, 1988), later the relevant species could not be identified with certainty (Gjerde et al, 2017b).…”
mentioning
confidence: 99%
“…Other authors have applied methods apart from species-specific PCR, such as cloning, and metabarcoding, to detect Sarcocystis spp. from samples containing oocysts or sporocysts [ 60 , 61 , 62 , 63 ]. However, previously conducted studies were also limited and revealed only a partial diversity of Sarcocystis spp.…”
Section: Discussionmentioning
confidence: 99%